2010
DOI: 10.3233/ao-2010-0074
|View full text |Cite
|
Sign up to set email alerts
|

A perdurant ontology for interoperating information systems based on interlocking institutional worlds

Abstract: In this work we have developed a formal ontology for perdurants suitable for representing interlocking institutional worlds in the general area of interoperating information systems. The formal ontology is a specialization of the perdurant elements of the DOLCE and Bunge-Wand-Weber universal formal ontologies using an abstract material ontology based on the theory of speech acts embodied in a method of information systems design taken from the literature. The perdurant formal ontology is necessarily integrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…For representing the perdurant part of domain ontology, a set of concepts based on the concepts of speech act can form a useful foundational ontology [38]. However, the general theory of speech acts covers a wide spectrum of phenomena.…”
Section: The Role Of Foundational Ontology In Domain Ontology Developmentioning
confidence: 99%
See 1 more Smart Citation
“…For representing the perdurant part of domain ontology, a set of concepts based on the concepts of speech act can form a useful foundational ontology [38]. However, the general theory of speech acts covers a wide spectrum of phenomena.…”
Section: The Role Of Foundational Ontology In Domain Ontology Developmentioning
confidence: 99%
“…These concepts of the domain are modeled at the conceptual level, using UML notation. Endurant ontology was modeled by UML class diagrams based on the UFO (Unified Foundational Ontology) foundational ontology [12], whereas perdurant ontology was modeled by UML activity diagrams based on the theory of DEMO (Design and Engineering Methodology for Organizations) [13,14], simplified by UML-based DEMO [38]. These conceptual models of the ontology are then transformed to be represented in the ontology implementation languages.…”
Section: Design and Developmentmentioning
confidence: 99%
“…Colomb and Ahmad [12] discussed the ontological approach from the perdurant or process perspective. It was expected that a perdurant ontology which resides at the upper layer ontology would be stable and invariant in interoperating activities, which is crucial in the disaster management scenario.…”
Section: Ontologymentioning
confidence: 99%
“…To build such a crisis ontology, many authors such as Colomb and Ahmad (2010) and Silva Parreiras and Staab (2010) have suggested (i) using a UML class model to build the meta-model, and (ii) using an OWL representation language to create the ontology on the basis of a previous meta-model. Silva Parreiras and Staab (2010) even proposed an integrated use of both modelling approaches in a coherent framework.…”
Section: Ontology and Meta-modellingmentioning
confidence: 99%
“…The second step of the ontology-building phase consists in transforming the previous knowledge into formal models. To do this, as suggested by Colomb and Ahmad (2010) and Silva Parreiras and Staab (2010), UML class diagrams and OWL have been chosen as ontology representation languages. The third step of the ontologybuilding phase consists in populating the obtained architecture with concrete knowledge.…”
Section: Ontology Engineeringmentioning
confidence: 99%